2015
DOI: 10.1002/cmdc.201500485
|View full text |Cite
|
Sign up to set email alerts
|

N‐Alkyl‐, 1‐C‐Alkyl‐, and 5‐C‐Alkyl‐1,5‐dideoxy‐1,5‐imino‐(l)‐ribitols as Galactosidase Inhibitors

Abstract: A series of 1,5-dideoxy-1,5-imino-(l)-ribitol (DIR) derivatives carrying alkyl or functionalized alkyl groups were prepared and investigated as glycosidase inhibitors. These compounds were designed as simplified 4-epi-isofagomine (4-epi-IFG) mimics and were expected to behave as selective inhibitors of β-galactosidases. All compounds were indeed found to be highly selective for β-galactosidases versus α-glycosidases, as they generally did not inhibit coffee bean α-galactosidase or other α-glycosidases. Some co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…A series of 1,5-dideoxy-1,5-imino-( l )-ribitol (DIR) derivatives carrying alkyl or functionalized alkyl groups were synthesized and evaluated for their glycosidase inhibitory capacity. 63 These molecules, which were designed as 4- epi -isofagomine ( 9 ) mimics, were found to be highly selective β-Gal inhibitors when compared to α-glycosidases; however, when considering the origin of the enzyme, the activity diminished in the coffee > almond > bovine > human series. The activity was markedly increased upon alkylation of the C5, with data suggesting that the “pseudo-anomeric” configuration of the series does not play a significant role.…”
Section: Chaperones As a Clinical Strategy For Lsds: Contributions Frmentioning
confidence: 99%
“…A series of 1,5-dideoxy-1,5-imino-( l )-ribitol (DIR) derivatives carrying alkyl or functionalized alkyl groups were synthesized and evaluated for their glycosidase inhibitory capacity. 63 These molecules, which were designed as 4- epi -isofagomine ( 9 ) mimics, were found to be highly selective β-Gal inhibitors when compared to α-glycosidases; however, when considering the origin of the enzyme, the activity diminished in the coffee > almond > bovine > human series. The activity was markedly increased upon alkylation of the C5, with data suggesting that the “pseudo-anomeric” configuration of the series does not play a significant role.…”
Section: Chaperones As a Clinical Strategy For Lsds: Contributions Frmentioning
confidence: 99%
“…Recent results by Martin and coworkers further support this notion. 108 These authors found that the galactoconfigured glycomimetic 4-epi-isofagomine (67), a strong inhibitor of b-Gal (IC 50 0.4 mM), was able to promote a 2.7-fold activity enhancement in GM1 fibroblasts harboring the R201C mutation when used at 10 mM concentration. Interestingly, the a-5-C-hexyl-DIR derivative 68 (Fig.…”
Section: Glycomimetic-based Pcs For G M1 -Gangliosidosismentioning
confidence: 99%
“…In particular, DCE usually induces different beneficial effects on both RAW 264.7 cells and HUVECs in the absence of cellular stress and apoptosis, By contrast to AC. Therefore, some DCE elements other than AC elements play are considered to play an important role as chemical chaperones to assist the functions of different signaling proteins in cells 42 and affect global protein expression in RAW 264.7 cells and HUVECs.…”
Section: Discussionmentioning
confidence: 99%